Abses Paru Pada Pasien Tuberkulosis Dengan Diabetes Melitus Yang Tidak Terkontrol - Efiyanti, Christy; Prawiro, Asysyukriati; Syahbunan, Khansa Kiasati Chandra; Rusmajati, Jetty; Rukmi, Kartika Widya; Kemuning, Asri Ragil; Desdiani, Desdiani (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The coexistence of tuberculosis (TB) and diabetes mellitus (DM) increases the risk of severe lung complications such as pulmonary abscess. Aim: This study evaluates the outcomes of such cases, emphasizing the effectiveness of combined therapeutic approaches. Methods: This retrospective study reviewed 121 patients diagnosed with TB and DM treated at a hospital in Depok City between January 2023 and April 2024. The study included four patients with confirmed lung abscesses. Diagnosis was established using clinical and supporting examination analyses. We monitored the patients for up to nine months after initiating treatment. All patients received standard TB and DM therapy along with intravenous antibiotics for two weeks and continued with oral antibiotics for six weeks. Results: Radiological findings consistently showed lung cavities with fluid levels and thick walls. Clinical outcomes demonstrated substantial improvement in all cases, with resolution of abscesses and symptom alleviation. Patients with lung abscesses who received early, combination treatment with antibiotics and medication for TB and DM had positive results. Conclusion: In our study, the administration of antibiotics for eight weeks, alongside simultaneous treatment for TB and DM, led to significant clinical improvement. Further research is warranted to management of lung abscesses in patients with TB and DM and intravenous antibiotics as the first-line approach.